Peran Akun @kitabisacom dalam Kampanye Sosial di Instagram - Wicaksana, Wily Taqwa; Adiprabowo, Vani Dias (Jurnal Pustaka Komunikasi, 2025)
This study aims to explore the role of @kitabisacom in social campaigns, focusing on the message communication advantages. This instagram platform serves as the primary research object to assess its success in delivering social campaign messages to the broader public. The method employed is content analysis of campaign messages disseminated through Instagram account @kitabisacom. Data were collected from various campaigns conducted within a specific period and analyzed to identify the types of messages conveyed, communication strategies employed, and the responses received from the public. The findings indicate that @kitabisacom effectively plays a significant role as a tool for disseminating social campaign messages. However, the study also identifies challenges such as message sustainability and optimizing message reach that need further attention to enhance impact and greater public engagement. These findings provide crucial insights into how digital platforms like @kitabisacom can be utilized effectively in social campaigns, highlighting the importance of employing appropriate communication strategies to achieve desired social goals.